Más allá del crew: El hip-hop y la profesionalización en la Ciudad de México - Green, Andrew (El Colegio de México, 2023)
In recent years, professionalization has become an increasingly influential concept in the Mexico City hip-hop scene. This article links professionalization to a decline in the influence of crews, rooted in fraternity, informality and shared identity, in favor of more formal ‘teams’ that are organized around solo artists. Based on ethnographic research, this article offers a framework through which the different conceptions of the ‘professional’ are considered: the formation of the object (that is, a ‘professional’ musical object) and the formation of the subject (that is, a ‘professional’ musician or musical actor). In this way, it shows the different ways in which professionalization not only incorporates and characterizes the ‘non-strategic’, but also distinguishes hip-hop’s ‘professionalism’ from the same ‘non-strategic’ characteristic.